RANCANG BANGUN SISTEM MONITORING KETINGGIAN AIR DAN KELEMBABAN TANAH PADA PENYIRAM TANAMAN OTOMATIS DENGAN HMI (HUMAN MACHINE INTERFACE) BERBASIS RASPBERRY PI MENGGUNAKAN SOFTWARE NODE-RED - Wiguna, Esa Hayyu; Subari, Arkhan (Vocational School Diponegoro University, 2017)
Esa Hayyu Wiguna, Arkhan Subari, in this paper explain that the monitoring system is a system used to monitor and control work processes in a plant design. This system is widely used and applied in the industrial world to find out the performance of a plant. To do the monitoring system, a lot of software can be used, which is then called the HMI (Human Machine Interface). The monitoring system with an interface in the form of HMI can be presented in various forms, such as buttons, or can also be displayed in the visualization of the plant while working. This monitoring system through an HMI interface uses supporting hardware in the form of a Raspberry Pi as a device to process the data that will be displayed on the display screen, while displaying its visualization uses an LCD touch screen. This LCD touch screen is connected to the Raspberry Pi via the LCD driver. The graphic form that will be displayed on the LCD touch screen is designed using Node-RED software. The visualization that will be displayed on the Touch Screen LCD will be adjusted to the working system of automatic plant sprinklers. This monitoring system using an HMI interface can display the plant's working system through indicators of water level and soil moisture. To test tube 2 water level measured through ultrasonic sensors through HMI has an error ratio of 1.01%, while for soil moisture measured through soil moisture sensors has an error ratio of 1.51%.